RADEN ADJENG KARTINI: BETWEEN EDUCATION AND FEMINISM IN LETTERS OF A JAVANESE PRINCESS (Martabat: Jurnal Perempuan dan Anak, 2019)
Kartini is one of Indonesian heroines. She was the pioneer in woman’s emancipation in Indonesia who lived in early 1900. Her brilliant thought was written in her letters. Although, she was living surround by thick walls during her growth of the culture. But, her reading helped her thinking that women should not give up to fight for their freedom because women also have their rights like the right to choose their future, work, and to get education. Kartini did not only fight for feminism only, one of the important gifts from Kartini is her contribution in education world. So that, this research to describe of Kartini’s thoughts and struggles to devise a study of feminism that touch the roots of Indonesian culture. The research design used in this research is descriptive qualitative by using library research and textual approach. The procedures of collecting data is read frequently Letters of a Javanese Princess, finding out the data, selecting and taking the data concerning with the purpose of the study, rechecking the whole data to decrease or to avoid falsity. After collecting the data the researcher analyze the data by data reduction, data display, and data conclusion/ drawing verification